Socio-emotional benefits of middle-aged grandfathers in grandfather-grandchild interaction - Belizario, Ana Maria T.; Guevara, Louisa Marie V.
An important source of family support in the Philippines is the intergenerational family ties, where a growing trend of middle-aged grandfathers MGF play a role in rearing their grandchildren. The authors of this research describe the different activities and the socio-emotional benefits of the MGF from the interaction with their school-aged grandchildren SGC. A qualitative research used in-depth interviews of 20 middle-aged grandfathers from Metro Manila. The research shows that the MGF-SGC interaction revolves around activities that are recreational, spiritual, sharing stories of family lineage and identity, mentoring, and providing childcare support. Despite the presence of limiting factors such as distance, work, and schedule, socio-emotional benefits of the grandfathers are still present, such as having a positive perception of ones self, improvement in ones ability to cope with stress, and promotion of ones social interaction with other people. The socio-emotional benefits of the grandfather-grandchild interaction were present to all grandfathers, despite differing in frequencies of interaction and living arrangements with the grandchild. For recommendations, the researchers suggest to address factors such as: 1. co-residency, 2. working and non-working grandfathers, 3. sampling size, 4. perspectives from both grandchild and grandfather, and 5. the use of quantitative method to determine interaction patterns.